Agreement between various measurements of standardised uptake value normalised by lean body mass in detecting background 18F-FDG activity in PET/CT oncologic imaging - Mohad Azmi, Nur Hafizah (2018)
PET/CT Scan is a diagnostic imaging tool predominantly used in oncology cases. Standardised uptake value (SUV) is the widely accepted method to quantitatively assess lesions detected on PET/CT. There is a limitation to the utility of this method, however, as this value becomes falsely reduced in overweight patients. Thus, we propose another quantitative method of using Standard Uptake Lean Body Mass (SUL) which can give a more consistent reading in patients having extremes of body mass index (BMI) values. As the prevalence of obesity is rising in this current decade, the utility of SUL becomes more relevant and necessary. This study correlated SUV and SUL values using the liver as a baseline reference organ and identified the pattern of distribution across various BMIs. There have been some studies that assessed the variations of SUV and SUL in obese subjects, but there have not been any studies that analysed whether there is a significant difference in SUL in subjects who undergo contrast-enhanced PET/CT. Interestingly, this study confirmed that SUL reading is consistent even among overweight patients and the utility of contrast media in PET/CT scans does not significantly differ from low dose non-contrast-enhanced scans.